Oncolytic Sendai virus‐induced tumor‐specific immunoresponses suppress "simulated metastasis" of squamous cell carcinoma in an immunocompetent mouse model. Issue 6 (8th January 2019) - Tanaka, Yuya; Araki, Koji; Tanaka, Shingo; Miyagawa, Yoshihiro; Suzuki, Hiroshi; Kamide, Daisuke; Tomifuji, Masayuki; Uno, Kosuke; Harada, Eiko; Yamashita, Taku; Ueda, Yasuji; Inoue, Makoto; et al.
Abstract: Background: The objectives of this study were to demonstrate anti‐metastatic effect of BioKnife, uPA activity‐dependent oncolytic Sendai virus, after BioKnife treatment for primary tumor, and analyze its mechanisms in a simulated metastasis mouse model of head and neck squamous cell carcinoma (HNSCC). Methods: We established a simulated metastasis mouse model using a murine HNSCC cell line "SCCVII." We assessed a tumor size and an induction of tumor‐specific immunoresponses using cytotoxic T‐lymphocyte (CTL) assay, flow cytometry (FCM) in spleen and immunohistochemistry (IHC) in secondary tumor. Results: Secondary tumors were significantly smaller in BioKnife‐treated group. CTL activities were significantly improved in BioKnife group. FCM revealed that induction of dendritic cells and CD4 + /CD8 + lymphocytes was significantly higher in BioKnife group. IHC showed that CD8 + lymphocytes invaded secondary tumor. Conclusion: Tumor‐specific immunoresponses induced by BioKnife has great potential to be a novel, safe, and less invasive option for control and prevention of metastasis.